Ashy Dermatosis: Suatu Laporan Kasus Jarang - Fatimah Fitriani; Moerbono Mochtar (MEDICINUS, 2024)
Background: Ashy dermatosis is a rare, acquired, benign, and idiopathic hypermelanotic disease. It is manifested asashy-colored lesion with no signs of inflammation. Commonly affected sites of the body include the trunk, neck, face, also proximal and distal extremities. Case: A 33-year-old woman came to Dr. Moewardi Hospital, Surakarta, with chief complaints asymptomatic, ashy colored macule that appear on her right arm. Physical examination in general region shows ashy-colored macule and multiple discrete patches of hyperpigmentation with irregular border. Dermoscopy examinationmacules showed bluish-gray skin markings over bluish background. Histopathological examination showed thin epidermis layer, hyperkeratosis, incontinentia pigmenti, dropping melanin resembles the basal layer civatte bodies. At dermis focal fibrosis was found with infiltrates, incontinentia pigmenti, and dropping melanin. Discussion: Ashy dermatosis or known as erythema dyschromicum perstans is a rare hyperpigmentation disorder that started with reddish, active-bordered lesions, then disappear, leaving a round or oval shape, polycyclic, and ashy macule on the proximal region of the trunk andneck. Onset of symptoms usually at young adult, between first and second decade of life. Etiology of ashy dermatosis is still unclear, and many factors were thought to be involved. Dermoscopy examination showed bluish-gray macules overbluish background. Histopathological examination showed lichenoid reactions and an increase melanin on the dermis. This report aims to describe the diagnosis a rare condition based on anamnesis, physical examination, dermoscopy, and histopathological examination. Clinical findings in this patient were in accordance with the result of previous studies.